Estudio de la calidad del agua de efluentes líquidos en mineras auríferas. - Juárez Gamboa, Claudia Zara (2011)
This issue relates to the study of water quality of liquid effluents in mining Auriferous to develop it was initially considered fundamental theoretical principles involving environmental knowledge in mining, in which the procedures of how to handle described the environmental problem of water pollution at various stages such as: mining project, mining operation and mine closure. The problem of environmental pollutants .the in the Peruvian mining activity. Studies conducted by the Environment Directorate of the Ministry of Health of Peru, refers to pollutants in the effluent water course, which are caused for three basic stages of mining: exploration, extraction and processing. These last two stages are the most significant, because in them are florescientes the main sources of pollution of rivers, lakes, ponds, etc., because of the deficiencies in the preparation and treatment of solid and liquid waste product of metallurgical operations presenting mining industries.